2011
DOI: 10.5194/hess-15-2551-2011
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved inorganic carbon export from carbonate and silicate catchments estimated from carbonate chemistry and δ<sup>13</sup>C<sub>DIC</sub>

Abstract: Abstract. This work presents a study of the dissolved inorganic carbon (DIC) exchange associated with groundwater discharge and stream flow from two upstream catchments with distinct basement lithologies (silicate vs. carbonate). The effects of catchment lithology were evident in the spring waters showing lower δ 13 C DIC and alkalinity (−16.2 ± 2.7 ‰ and 0.09 ± 0.03 meq l −1 , respectively) in the silicate and higher values (−9.7 ± 1.5 ‰ and 2.0 ± 0.2 meq l −1 ) in the carbonate catchment.The streams exhibite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Carbon export demonstrated significant interannual variability and long‐term trends in eastern North America from 1901 to 2008. Environmental factors affected the temporal patterns of riverine carbon fluxes either through influencing hydrological processes or by changing carbon leachate production and transport [ Clair and Ehrman , ; Raymond et al , ; Shin et al , ; Tranvik and Jansson , ]. Results of this study indicated that factors such as climate variability and land use/cover change played the most important role in variability and trends over time.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon export demonstrated significant interannual variability and long‐term trends in eastern North America from 1901 to 2008. Environmental factors affected the temporal patterns of riverine carbon fluxes either through influencing hydrological processes or by changing carbon leachate production and transport [ Clair and Ehrman , ; Raymond et al , ; Shin et al , ; Tranvik and Jansson , ]. Results of this study indicated that factors such as climate variability and land use/cover change played the most important role in variability and trends over time.…”
Section: Discussionmentioning
confidence: 99%
“…4, where the CaCO 3 was the dominant source (also during the dry season). [Colour figure can be viewed at wileyonlinelibrary.com] 2431 DISSOLVED INORGANIC CARBON VARIATIONS IN A KARSTIC CATCHMENT uptake of carbon by photosynthesiscan lead to isotope fractionation (Telmer and Veizer, 1999;Wachniew, 2006;Shin et al, 2011;Dang et al, 2018) and thus bring uncertainties to the above estimation, more detailed studies are urgently needed to reduce these uncertainties.…”
Section: Dynamics Of Dic Sourcesmentioning
confidence: 99%
“…Stable carbon isotope ratio (δ 13 C) can be used as a tracer to study weathering and riverine carbon cycles as a result of the isotopic differences between carbonate and biological carbon. Marine carbonate bedrock sources have typical δ 13 C of 0‰ (Clark and Fritz, 1997;Shin et al, 2011). The δ 13 C of atmospheric CO 2 is currently approximately À8.2‰, which is a decrease from À7.6‰ in the 1980s (Cuntz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ever-increasing concerns regarding excess atmospheric CO2 affecting the environment, multiple studies have suggested that karst systems can serve as carbon sinks (Li et al 2008a;Cuezva et al 2011;Gorka et al 2011;Shin et al 2011;White 2013;McClanahan et al 2016;Jiang 2013;Zhang et al 2015;Zeng et al 2016). These studies attempt to delineate carbon fluctuations within karst systems to better understand carbon sequestration from the atmosphere.…”
Section: Co2 Dissolution Kineticsmentioning
confidence: 99%
“…One of the greatest factors influencing the depletion or enrichment of 13 C is soil-derived microbial activity (Telmer and Veizer 1999;White 2013;Zhang et al 2015). This variance is primarily due to the type of plant vegetation (C3 vs C4) that has a direct bearing on the fractionation of carbon isotopes ( 12 C vs 13 C) being used by the vegetation (Drever 1997;Li et al 2008a;Hoefs 2010;Lambert and Aharon 2010;Gorka et al 2011;Shin et al 2011;Florea 2013;White 2013;McClanahan et al 2016).…”
Section: δ 13 Cdic Isotope Sourcing and Fluxmentioning
confidence: 99%